1993
DOI: 10.1063/1.353841
|View full text |Cite
|
Sign up to set email alerts
|

Displacement current and multiple pulse effects in plasma source ion implantation

Abstract: Articles you may be interested inEffects of long pulse width and high pulsing frequency on surface superhydrophobicity of polytetrafluoroethylene in quasi-direct-current plasma immersion ion implantation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…It is indeed possible that the duty cycle is sufficiently high, hence, the sheath of successive pulses propagate in increasingly thinner plasma, and thus the sheath edge extents further from the surface with each pulse until equilibrium is reached between "pumping" of ions by the bias pulse and supply by the plasma. Such multiple-pulse effects have been modeled for plasma immersion ion implantation using a particle-cell-code [29] but the principle also applies to other pulsed systems like pulsed sputtering.…”
Section: Transient Sheathsmentioning
confidence: 99%
“…It is indeed possible that the duty cycle is sufficiently high, hence, the sheath of successive pulses propagate in increasingly thinner plasma, and thus the sheath edge extents further from the surface with each pulse until equilibrium is reached between "pumping" of ions by the bias pulse and supply by the plasma. Such multiple-pulse effects have been modeled for plasma immersion ion implantation using a particle-cell-code [29] but the principle also applies to other pulsed systems like pulsed sputtering.…”
Section: Transient Sheathsmentioning
confidence: 99%
“…Since ion transit time across the sheath is large (on the order of 1/X p ) and sheath expands during ion flight across the sheath, both the shape and magnitude of the potential barrier vary, so that the implanted ions do not get the full bias voltage. In other words, displacement current across the expanding sheath leads to an increase in the ion implanted current and causes a decrease in the implanted ion energy with respect to the stationary sheath with the same parameters [19,20]. According to Fig.…”
Section: Fluid Model and Basic Equationsmentioning
confidence: 99%
“…Experimental study [11] have shown that large deviations in the retained dose could be observed in dependence on the sample geometry and plasma sheath thickness. Experiments for determining the dose distribution are very complicated so that various computer programs for simulating the implantation were developed [8]- [10], [12]- [17]. A self-consistent 3D calculation of the sheath dynamics and ion current is prohibitively time-consuming.…”
Section: Plasma Sheath Dynamicsmentioning
confidence: 99%